CXCR6+ and NKG2C+ Natural Killer Cells Are Distinct With Unique Phenotypic and Functional Attributes Following Bone Marrow Transplantation - Aviles-Padilla, Kevin; Angelo, Laura S.; Fan, Dwight; Paust, Silke (Frontiers in Immunology, 2022)
Reactivation of human cytomegalovirus (HCMV) is a life-threatening complication in transplant patients. Natural Killer (NK) cells are the first lymphocyte lineage to reconstitute following an allogeneic hematopoietic stem cell transplant (HSCT). Amongst them, NK cell Group 2 isoform C/ Killer cell lectin-like receptor subfamily C, member 2 (NKG2C)-expressing NK cells contribute significantly to patient protection upon HCMV reactivation. NKG2C+ NK cells are capable of immunological memory, albeit NK cell memory is not restricted to them. Hepatic C-X-C Motif Chemokine Receptor 6 (CXCR6)-expressing NK cells also mediate memory responses in mice and humans. Small numbers of them circulate and can thus be studied in peripheral blood samples. We hypothesize that NKG2C+ and CXCR6+ NK cell subsets are distinct. To test our hypothesis, we used multi-parametric flow cytometry to determine the phenotypes and effector functions of CD56bright vs. CD56dim and NKG2C+ vs. CXCR6+ human NK cell subsets in the peripheral blood (PB) of pediatric transplant recipients monthly while monitoring patients for HCMV reactivation. Interestingly, we did not find any NKG2C+CXCR6+ NK cells in the transplant recipients’ peripheral blood, suggesting that NKG2C+ and CXCR6+ NK cells are distinct. Also, NKG2C–CXCR6– NK cells, rather than NKG2C+ NK cells, made up most NK cells post-transplant, even in transplant recipients with HCMV viremia. In contrast to NKG2C+ NK cells, CXCR6+ NK cells appeared phenotypically less differentiated but were highly proliferative and produced IFN- and TNFα. Our findings contribute to our understanding of post-transplant NK cell development and its implications for human health.